Public demand for social investment: new supporting coalitions for welfare state reform in Western Europe?. Issue 6 (3rd June 2018) - Garritzmann, Julian L.; Busemeyer, Marius R.; Neimanns, Erik
ABSTRACT: Social investment has recently received much attention among policy-makers and welfare state scholars, but the existing literature remains focused on policy-making on the macro level. We expand this perspective by studying public opinion towards social investment compared to other welfare policies, exploiting new public opinion data from eight European countries. We identify three latent dimensions of welfare state preferences: 'social investment'; 'passive transfers'; and 'workfare' policies. We find that social investment is far more popular compared to the other two. Furthermore, we identify distinct supporting groups: passive transfer policies are most supported by low-income, low-educated people, by individuals leaning towards traditional social values and by those subscribing to left-wing economic attitudes. Social investment policies are supported by a broad coalition of individuals with higher educational backgrounds and left-libertarian views from all economic strata. Workfare policies are most popular with high-income individuals and those subscribing to economically conservative and traditional authoritarian values.